Clinical implications of remote dielectric sensing system to estimate lung fluid levels. Issue 3 (March 2023) - Imamura, Teruhiko; Narang, Nikhil; Kinugawa, Koichiro
Summary: The reduction of pulmonary congestion is an essential clinical target in the management of chronic heart failure. This proves to be challenging given the lack of a gold standard method to quantify the degree of pulmonary congestion both quickly and non-invasively. Remote dielectric sensing (ReDS) is a non-invasive electromagnetic energy-based technology to quantify lung fluid levels as a percentage within minutes. This technique, due to its high negative predictive value, may be a useful tool particularly to rule out primarily cardiac causes of dyspnea in ambulatory patients when the values are normal. Further studies are warranted to establish ReDS-guided management of congestive heart failure patients. Graphical abstract: Unlabelled Image Highlights: Remote dielectric sensing (ReDS) is a non-invasive electromagnetic energy-based system to quantify lung fluid. ReDS values have correlations with other pulmonary congestion-related modalities. ReDS-guided management of congestive heart failure patients is the next concern.